2015
DOI: 10.1007/s12098-015-1851-y
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attention Deficit Hyperactivity Disorder and Parenting Styles

Abstract: The aim of the present study was to compare the parenting styles in parents with and without adult attention deficit hyperactivity disorder (ADHD) who had children with ADHD. It was a case-control study with convenience sampling strategy. Participants were recruited from the parents of previously diagnosed children with ADHD referred to Imam Hossein Hospital, Tehran/ Iran. Ninety parents with adult ADHD and 120 normal parents were chosen by Conner's Adult ADHD Screening Scale (CAARS) and psychiatrist interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
(11 reference statements)
0
0
1
Order By: Relevance
“…Whereas, when the perception of children regarding parenting style was interviewed by Bhuiyan et al (2020), in Dhaka among normal adolescent people found the majority, 40.0% of parents followed permissive style, 25.8% authoritative and 25.3% followed authoritarian parenting based on Perceived Parenting Style Scale [20]. Contrary to our current finding, Karbalaei et al (2016), in their analysis showed parents with ADHD applied the Authoritarian parenting style significantly more than normal parents [21].…”
Section: Discussioncontrasting
confidence: 87%
“…Whereas, when the perception of children regarding parenting style was interviewed by Bhuiyan et al (2020), in Dhaka among normal adolescent people found the majority, 40.0% of parents followed permissive style, 25.8% authoritative and 25.3% followed authoritarian parenting based on Perceived Parenting Style Scale [20]. Contrary to our current finding, Karbalaei et al (2016), in their analysis showed parents with ADHD applied the Authoritarian parenting style significantly more than normal parents [21].…”
Section: Discussioncontrasting
confidence: 87%